Kinetic Study and Modeling of Wild-Type and Recombinant Broccoli Myrosinase Produced in E. Coli and S. Cerevisiae as a Function of Substrate Concentration, Temperature, and Ph - Castillo-Nara, A; Mahn-Osses, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The myrosinase enzyme hydrolyzes glucosinolates, among which is glucoraphanin, the precursor of the anticancer isothiocyanate sulforaphane (SFN). The main source of glucoraphanin is Brassicaceae; however, its natural concentration is relatively low, limiting the availability of SFN. An option to obtain SFN is its exogenous production, through enzymatic processes and under controlled conditions, allowing complete conversion of glucoraphanin to SFN. We characterized the kinetics of wild-type (BMYR) and recombinant broccoli myrosinases produced in E. coli (EMYR) and S. cerevisiae (SMYR) in terms of the reaction conditions. Kinetics was adjusted using empirical and mechanistic models that describe reaction rate as a function of substrate concentration, temperature, and pH, resulting in R2 values higher than 90%. EMYR kinetics differed significantly from those of BMYR and SMYR probably due to the absence of glycosylations in the enzyme produced in E. coli. BMYR and SMYR were subjected to substrate inhibition but followed different kinetic mechanisms attributed to different glycosylation patterns. EMYR (inactivation Ea = 76.1 kJ/mol) was more thermolabile than BMYR and SMYR. BMYR showed the highest thermostability (inactivation Ea = 52.8 kJ/mol). BMYR and EMYR showed similar behavior regarding pH, with similar pK1 (3.4 and 3.1, respectively) and pK2 (5.4 and 5.0, respectively), but differed considerably from SMYR. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.